EPISTEMOLOGICAL STUDIES OF TAFSEER WITHOUT DOTS DÛRR AL-ASRᾹR BY MAHMUD IBN MUHAMMAD AL-HAMZAWI - Ahmad Yahya; Roem Rowi; Abd Kholid (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2020)
The study of Dûrr al Asrār's interpretation epistemology by Mahmud Ibn Muhammad al Hamzawi is important because it has a special method that is rarely used by the majority, namely interpreting the Quran by using letters without dots. The use of this kind of interpretation seems to limit the interpreter in using the source of it and raises the hypothesis that this is a pure interpretation of bi al-ma 'qul. The focus of this study is to examine the sources, methods, and validity of interpretation. By descriptive analysis, this study concludes that the epistemological basis of Dûrr al Asrār by Mahmud Ibn Muhammad al Hamzawi is a combination of bi al-ma'tsur and bi al ma'qul, both of which dominate the language source, so this is called tafsir bi al-ma ' qul or bi al-ra'y. This method is globally and in lughawi and fiqhi styles. While the validity of Mahmud Ibn Muhamamd al-Hamzawi's interpretation after being tested with the theory of al-Asil wa al-Dakhil Abdul Wahab fayed, this is included in the authentic interpretation, both in the source of the interpretation and the object of al-Dakhil which is not in it.